AKTIVITAS ANTIJAMUR EKSTRAK ETANOL DAUN KESUM (Polygonum minus Huds.) TERHADAP Microsporum canis - Vica Vionita Rosalim; Syarifah Nurul Yanti Rizki Syahab Asseggaf; Diana Natalia; Mahyarudin Mahyarudin (Jurnal Fitofarmaka Indonesia, 2019)
Dermatophytosis is a fungal infection caused by one of the superfixial mycoses, namely dermatophytes. Microsporum canis is one of the dermatophyte species that can infect hair, skin, leg and thighs. Kesum plants (Polygonum minus Huds.) are endemic plants of West Kalimantan that have many bioactive compounds from the roots to the leaves. The leaves of kesum contain secondary metabolites which can inhibit fungi growth. This research had purpose to know  the antifungal activity of kesum leaves’ ethanol extracts on Microsporum canis. The kesum leaves’ extraction  used maceration method with 96% ethanol as a solvent. Analysis secondary matbolites of kesum leaves’ secondary metabolites used tube test and thin layer chromatography. Antifungal activity test used Kirby-Bauer disk diffusion method with 5 extract concentration variantions i.e. 80, 40%, 20%, 10%, and 5%. Itraconazole 8 µg/disk was used as a positive control and DMSO 10% was used as a negative control. Kesum leaves’ ethanol extract was obtained saponin, flavonoid, alkaloid, therpenoid, and phenol. Ethanol extracts of kesum leaves did not create zone of inhibition against Microsporum canis. Ethanol extracts of kesum leaves didn’t have antifungal activity against Microsporum canis.